Salvianolic Acid B Promotes the Survival of Random-Pattern Skin Flaps in Rats by Inducing Autophagy - Lin, Jinti; Lin, Renjin; Li, Shihen; Wu, Hongqiang; Ding, Jian; Xiang, Guangheng; Li, Shi; Wang, Yiru; Lin, Dingsheng; Gao, Weiyang; Kong, Jianzhong; Xu, Huazi; et al. (Frontiers in Pharmacology, 2018)
Random-pattern skin flap transplantation is frequently applied in plastic and reconstructive surgery. However, the distal part of the flap often suffers necrosis due to ischemia. In this study, the effects of salvianolic acid B (Sal B) on flap survival were evaluated, and the underlying mechanisms were investigated. Sal B improved the survival area, reduced tissue edema, and increased the number of microvessels in skin flaps after 7 days, whereas an autophagy inhibitor (3-methyladenine) reversed the Sal B-induced increase in flap viability. In addition, Sal B stimulated angiogenesis, inhibited apoptosis, reduced oxidative stress, and upregulated autophagy in areas of ischemia. Moreover, the effects of Sal B on angiogenesis, apoptosis, and oxidative stress were reversed by autophagy inhibition. Overall, our findings suggest that Sal B has pro-angiogenesis, anti-apoptosis, and anti-oxidative stress effects by stimulating autophagy, which enhances the survival of random-pattern skin flaps.